Pedagogical Heritage of A.S. Makarenko in Modern Educational Space - BAZALEY, Elena (Journal of Education, Technology and Computer Science, 2013)
This article deals with the research of pedagogical heritage of A.S. Makarenko. He took great care of mora1 and labor upbringing of pupils. Teaching senior pupils we think it is necessary to ensure knowledge of last epochs teachers whose ideas are actual today. As our research is based on Makarenko’s creative heritage we shall follow the process of pedagogical formation of a future teacher today.